Are newer insulin analogues better for people with Type 1 diabetes?. Issue 4 (21st January 2019) - Misra, S.; Mathieu, C.
Abstract: Achieving optimal blood glucose control in Type 1 diabetes is a delicate balance between ensuring tight glycaemic control and achieving this without the expense of hypoglycaemia and weight gain, two major factors impacting quality of life. This is a real challenge for people with Type 1 diabetes and underpins many of the struggles they face in self‐managing on a day‐to‐day basis. The main goals of insulin delivery are to try to simulate the physiology of β‐cell insulin secretion as closely as possible and to overcome the challenges of peripheral insulin administration by achieving rapidity of onset with mealtime insulins and stability of the glucose‐lowering effects of long‐acting insulins. Since the early days of human insulin use, there have been many developments in insulin formulations that aim to achieve these goals as much as possible, thus contributing to better glycaemic control whilst minimizing hypoglycaemia. In the present review we discuss the currently available insulin analogues and the challenges of achieving glucose control using current analogues in those on multiple daily injections, and appraise the evidence base for newer‐generation insulin analogues, such as insulin degludec, glargine U300, faster‐acting insulin aspart and BioChaperone lispro. We also highlight new insulins in development and unmet needs in people with Type 1 diabetes. What's new?: In people with Type 1 diabetes the aim is to optimize insulin delivery in order to balance successfully the risk of hypoglycaemia whilst maintaining tight glycaemic control. Many new insulin analogues are available for people with Type 1 diabetes, including more rapidly acting mealtime insulins and longer‐acting and more concentrated basal insulins. In this review, we discuss the challenges of insulin delivery using first‐generation insulin analogues and the potential benefits and disadvantages of newer agents, and assess the risk of hypoglycaemia and safety of all insulin analogues.